A striatal interneuron circuit for continuous target pursuit - Namsoo Kim (Nature Portfolio, 2019)
Many natural behaviours involve tracking of a target in space. Here, the authors describe a task to assess this behaviour in mice and use in vivo electrophysiology, calcium imaging, optogenetics, and chemogenetics to investigate the role of the striatum in target pursuit.